Discussion On the Platform System of Teaching Chinese As A Foreign Language On The Internet - Xiao Dong; Chen Aijing (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Affected by the epidemic of New Coronavirus pneumonia, the universities have been teaching online for one semester without dropping the progress of teaching. But what is the effect of extensive online teaching for students and what needs to be improved? This research was carried out in response to these. The survey results show that in online teaching, live + online interaction is more popular with students, and most students' autonomous learning ability has been improved, but there are still big problems in the connection of knowledge points. Most students want to interact more with teachers. Teachers should pay attention to combing knowledge points and their relationships, distinguish between basic and difficult points, and improve students' enthusiasm, And can regularly organize voice calls to answer questions to solve students' doubts. This paper discusses the platform system of teaching Chinese as a foreign language on the Internet, so as to provide reference for teachers' teaching in the future.